Pathogenesis of postantibiotic diarrhoea caused by Clostridium difficile: an in vitro study in the rabbit intestine. Issue 5 (May 1988) - Guandalini, S; Fasano, A; Migliavacca, M; Verga, M C; Mastrantonio Gianfrilli, P; Ferrara, A; Alessio, M; Malamisura, B; Galati, P; Pantosti, A
Abstract : To elucidate the pathophysiological changes leading to postantibiotic diarrhoea caused by Clostridium difficile and its cytotoxin, oral ampicillin was given to rabbits, and jejunal, ileal, and caecal segments of those that developed diarrhoea were investigated in vitro. The rabbits that, in response to treatment, harboured Clostridium difficile in their colonic lumen were studied, and the results expressed according to the presence or absence of Clostridium difficile and/or its cytotoxin. Thus, we refer to either CD+ or CD- segments. The influx of glucose, phenylalanine, glycylphenylalanine, and lysine across the brush border of jejunum and ileum of CD+ segments was severely impaired, while only slightly blunted in CD-. No significant change was detected in the influx of glutamic acid in the jejunum of all treated animals and in the CD- ilea. Morphologic damage in ileum and caecum of CD+ was also more evident than in CD-. Transepithelial ion transport across short circuited ileal mucosa (CD+ and CD-) revealed secretory changes in Cl net transport that were more marked in CD-. We conclude that: (1) Clostridium difficile may also colonise the upper intestinal tract, where it induces morphological and functional damage, severely impairing nutrient absorption; and (2) the ileum contributes to the diarrhoea caused by CD even when the micro-organism is confined to the more distal gut by showing moderate impairment of nutrient absorption and marked electrolyte secretion.